The impact of the war on Syria on the level of food living in Syria (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The case of secular nutriment living standard is one of the major challenge which confronts any country as one of the basic national security a from an economic perspective the lack of nutrition safety is a result of the disability of agricultural sector to achieve the rising consumption of production to face the increasing request for food which leads to a big gap in living standardThe study reached a conclusion which is to increase the living standards for the citizen can be achived by getting the goods needed and to increase salary rate and offer job applicationIn addition the national nutrition programme should be activated which aims the improve the living nutrition standard for the rural families, through increasing production in the fileds of good jobs and activating the research programmes in agriculture.